2017
DOI: 10.1016/j.rmcr.2017.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Chronic eosinophilic pneumonia: Adjunctive therapy with inhaled steroids

Abstract: Idiopathic chronic eosinophilic pneumonia (ICEP) is a rare form of diffuse parenchymal lung disease first identified by Carrington et al. in 1969. It is characterized by the presence of constitutional and respiratory symptoms with associated peripheral opacities on imaging and elevated serum and/or bronchoalveolar eosinophilia. Although data is limited regarding etiology or prevalence, it is known that ICEP has a 2:1 female: male predominance and typically affects non-smokers. Diagnosis rests on the clinical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“… 1 , 3 Other such causes of eosinophilic pneumonia that need to be excluded prior to diagnosis include but not limited to drug‐induced eosinophilic pneumonia, eosinophilic granulomatosis with polyangiitis (EGPA, also known as Churg Strauss), allergic bronchopulmonary aspergillosis (ABPA), and fungal and parasitic infections depending on exposure history. 3 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 1 , 3 Other such causes of eosinophilic pneumonia that need to be excluded prior to diagnosis include but not limited to drug‐induced eosinophilic pneumonia, eosinophilic granulomatosis with polyangiitis (EGPA, also known as Churg Strauss), allergic bronchopulmonary aspergillosis (ABPA), and fungal and parasitic infections depending on exposure history. 3 …”
Section: Discussionmentioning
confidence: 99%
“…There are no absolute diagnostic criteria for ICEP but diagnosis is made based on respiratory symptoms for at least 2 weeks, presence of multilobar peripheral ground-glass opacities, and eosinophilia >40% on BAL or peripheral eosinophilia >1000/mm 3 in the absence of other eosinophilic lung diseases. 1,3 Other such causes of eosinophilic pneumonia that need to be excluded prior to diagnosis include but not limited to drug-induced eosinophilic pneumonia, eosinophilic granulomatosis with polyangiitis (EGPA, also known as Churg Strauss), allergic bronchopulmonary aspergillosis (ABPA), and fungal and parasitic infections depending on exposure history. 3 Once diagnosed and treatment is started, patients typically respond well to steroids with improvement in symptoms and rapid resolution of eosinophilia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…But other group considered inhaled steroids not effective [8]. Chan et al [9] reported a patient who underwent treatment with systemic corticosteroids followed by inhaled steroids and who remained in remission for 2 years. We tried 5 kinds of inhaled steroids during the active and the remission phases of eosinophilic pneumonia to avoid the adverse effects associated with systemic administration of steroids, but we could not achieve sufficient efficacy using inhaled steroids.…”
Section: Discussionmentioning
confidence: 99%